Effect of low temperature on the performance of carbo -based conductive ink for flexible printed circuit - Buyamin, Norsheila (2019)
Nowadays, it is known that printing methodologies can be used to print electrically functional devices on a variety substrates such as organic and inorganic substrate's materials. Currently, printing technologies have been an attractive alternative printing method to fabricate flexible electronic devices, keeping to its advantages including easy handling, wide use and low cost. However, using flexible substrate open up new possibilities for printed electronic (PE), where certain applications expose the flexible substrate to a mechanical bending which might decreased the performance or becomes a cause to a functionality. Moreover, developing of an appropriate ink at an extreme surrounding temperature with high conductivity and good dispersion of the ink-jet printing is one of the critical problems that need to be solved. Thus, the objectives of this study are determine the effects of cyclic loading on the elasticity and the conductivity of carbon-based conductive ink after exposing to low temperature. The sample of conductive ink has been tested by resistivity test, nanoindentation test and microstructure analysis after doing cyclic test. This study is focused on the conductivity behaviour of printed conductive ink after being exposed to two different temperature; low temperature at -6°C and room temperature at 26°C. After being exposed to each of the temperature set, the cyclic loading test of 1000 and 5000 cycles each was carried out where non-cyclic sample was prepare as the bench-marking sample. From the cyclic test result, it is understood that the resistivity of printed ink at low temperature is lower than that of at room temperature. Besides, the lowest resistivity is recorded as 105.71Q/sq for sample that being tested at 5000 cyclic after exposed to low temperature. This is due to the deformation of the elasticity properties of the ink when exposed to the low temperature after the printing process. On the other hand, the hardness of low temperature sample is larger than room temperature. However, the highest resistivity in this study is 5000 cyclic sample at room temperature almost 206.52Q/sq. Moreover, in cyclic test, the printed conductive ink will be bend and stretched at the maximum limit. Therefore, the surface structure become scratch and crack onto conductive ink. Finally, the 5000 cyclic sample at room temperature shows more defect on the surface structure than others.